1973
DOI: 10.1126/science.181.4104.1057
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer: Induction of Differentiation by Embryonic Tissue

Abstract: A mouse mammary tumor, adenocarcinoma BW 10232, was maintained in vitro for 14 days, separated from embryonic mammary mesenchyme by a Millipore filter. Tubules developed in the tumor; deoxyibonucleic acid synthisis declined; and a presumptive acid mucopolysaccharide matrix, not evident in the controls, appeared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

1982
1982
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(52 citation statements)
references
References 8 publications
1
51
0
Order By: Relevance
“…These studies have revealed that fibroblasts can both inhibit and enhance tumor growth. The cocultivation of fibroblasts with mammary carcinoma cells exhibits a more orderly histological differentiation (62,63) and basal cell carcinoma cells grown in association with stromal cells demonstrated a loss of their malignant properties (64). In contrast, other studies revealed that TAF have a growth-stimulating effect upon tumors in vitro (65)(66)(67) and in vivo (68 -70).…”
Section: Discussionmentioning
confidence: 99%
“…These studies have revealed that fibroblasts can both inhibit and enhance tumor growth. The cocultivation of fibroblasts with mammary carcinoma cells exhibits a more orderly histological differentiation (62,63) and basal cell carcinoma cells grown in association with stromal cells demonstrated a loss of their malignant properties (64). In contrast, other studies revealed that TAF have a growth-stimulating effect upon tumors in vitro (65)(66)(67) and in vivo (68 -70).…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30][31][32][33] Breast carcinoma cells exhibit a reduction in proliferation when cultured in the presence of normal breast mesenchymal cells. 26 In addition to effects on proliferation, normal stroma can also induce the differentiation of transformed cells. Work demonstrated that intestinal epithelial cell lines derived from colonic adenocarcinomas exhibit normal morphology and functional differentiation when cocultured with embryonic rat mesenchyme.…”
Section: The Role Of Stroma As a Tumor Suppressormentioning
confidence: 99%
“…However it is also important to note that the normal mammary gland microenvironment has inhibitory effect on breast cancer progression (DeCosse et al, 1973). This indicates that cancer cells can maintain their properties only in an abnormal microenvironment.…”
Section: Microenvironment Of Breast Cancer Cellsmentioning
confidence: 99%